Psychological Risk Factors for Worsening Prognosis of Diabetes Mellitus Patients during the COVID-19 Pandemic - Ubaidillah, Zaqqi; Wulandari, Ratna (Universitas Aisyah Pringsewu, 2024)
People with diabetes mellitus (DM) are prone to experiencing psychological problems during COVID-19 pandemic situation. This article examines various psychological risk factors experienced by people with diabetes mellitus during the COVID-19 pandemic. This study used a literature review method that was carried out by identifying articles in 5 databases, namely ScienceDirect, EBSCO, ProQuest, Google Scholar, and PubMed. The number of articles obtained from five databases was 788. The number of articles reviewed in full text was 61 and those that fit the inclusion and exclusion criteria were 24. The quality of articles was assessed using PRISMA based on predefined inclusion and exclusion criteria. Factors that influence the psychological condition of diabetes mellitus sufferers during the COVID-19 pandemic are concerns about a worse prognosis, difficulty managing diabetes during the pandemic, feelings of loneliness, and financial pressure. Stress and difficulties of diabetics in disease management can lead to hyperglycemia. Hyperglycemia is a risk factor for worsening prognosis in people with COVID-19. COVID-19 is a pandemic that can increase stress and difficulties for diabetics in diabetes management, and diabetes management can increase the risk of a worse prognosis for COVID-19, both of which are reciprocal mechanisms. So that the mental pressure felt by diabetics requires special attention and intervention from health workers. Diabetes self-management education should focus on diet, exercise, medication adherence, prevention of hypoglycemia, and healthy coping patterns. Teleconsultation can be an alternative in providing mental health services to diabetes mellitus sufferers during the COVID-19 pandemic.